Key compounds in plants eaten by Mongolian livestock during winter, Amygdalus pedunculata as an example (Journal of Eastern - Western Pharmacology and Pharmacy, 2025)
A wide varieties of plants are distributed across Mongolia, many of which serve as valuable medicinal and forage reserves for livestock in nomadic cultures. Their usage and characteristic features were investigated through the Science and Technology Research Partnership for Sustainable Development (SATREPS) program, conducted from 2020 to 2025. As part of this program, our group focused on studying and reporting the chemical constituents of these plants and their biological activities to understand the scientific basis underlying their traditional usages. A presentation at the conference, an overview of the SATREPS project, and its results will be presented. Among the various studies conducted, chemical constituents isolated from Amygdalus pedunculata, a valuable forage shrub, have been highlighted. The extract of A. pedunculata (a cyanogenic glycoside), namely prunasin, and four flavanones namely eriodictyol, naringenin, taxifolin, and aromadendrin were isolated as main constituents of the branches of A. pedunculata. These compounds may bring significance and effects on animals eating A. pedunculata.